Bioaccumulation of trace metal elements and biomarker responses in caged juvenile flounder at a polluted site: Effects of fish density and time exposure. (December 2022) - Diop, Mamadou; Couteau, Jérôme; Bado-Nilles, Anne; Tavernier, Eric; Ouddane, Baghdad; Denis, Jeremy; Duong, Gwendoline; Gevaert, François; Monchy, Sebastien; Laroche, Jean; Amara, Rachid
Abstract: This study investigates the effect of fish density and exposure duration on trace metal elements (TME) bioaccumulation and several biomarkers response. Juvenile flounders were caged at low, medium and high densities and exposed during 15 or 30 days in the Seine estuary. The concentrations of the TME measured in the muscle of the caged fish were all in agreement with their bioavailability percentage in the sediments. Higher concentrations of TME were found in flounders' muscle exposed for 15 days compared with those caged for 30 days. For the same exposure time, the density of fish had no effect on the accumulation of the TME in the flounders' muscle. Biomarkers responses varied according to density and duration of exposure. Special care should be taken in their interpretation. We underline that for an optimal assessment of TME pollution in the field, 15 days with low densities of fish per cage are sufficient. Highlights: Concentration of TME in caged fish depends on their bioavailability in the sediment. Concentration of TME was higher in fish caged during 15 days. Density of fish per cage had no effect on the accumulation of TMEs Density strongly impacted responses of fitness and innate immunity biomarkers. Fish in low density per cage exposed during 15 days assess well the TME pollution